Wells Syndrome with Multiorgan Involvement Mimicking Hypereosinophilic Syndrome - M. Carlesimo; L. Fidanza; E. Mari; G. Feliziani; A. Narcisi; G. De Marco; A. Bartolazzi; G. Camplone (Karger Publishers, 2009)
Eosinophil-associated diseases represent a spectrum of heterogeneous disorders, where blood and cutaneous eosinophilia is the most important feature and eosinophils are the principal cause of cutaneous lesions. These diseases show some similarities in the clinical features but also many distinctive characteristics [Saurat et al., Dermatologia e malattie sessualmente trasmesse, Milano, Masson, 2000]. Wells syndrome is one of these disorders and is an uncommon recurrent inflammatory dermatosis, rarely associated to signs and symptoms of multiple organ involvement [Arch Dermatol 2006;142:1157-1161]. Hypereosinophilic syndrome, in contrast, constitutes a group of idiopathic disorders characterized by blood eosinophilia for at least 6 months, associated with single or multiple organ system dysfunction [Arch Dermatol 2006;142:1157-1161]. Clinically atypical Wells syndrome with multiorgan involvement is reported here. A correct diagnosis is difficult in this case, but clinical and histopathological features are compatible with this diagnosis. The reported condition likely represents a borderline hypereosinophilic disease, in which clinical features of both hypereosinophilic syndrome and Wells syndrome are present.